.: False Negative Effect of Triglyceride on Vitamin D - Caglayan, Murat (Journal of Medical Biochemistry, 2022)
Background: Inaccurate test results may also be a reason why vitamin D deficiency is seen as a common problem in the world. Interferences from the sample matrix during testing are the most important factors of measurement error. In this study, the relevance between triglyceride and total cholesterol levels and vitamin D levels in Turkey was investigated. Methods: 25-hydroxyvitamin D (25-OHD) test results studied in Turkey in 2021 and blood lipid levels were compared. Data were obtained from the Ministry of Health National Health Database (THND). Simultaneously, 25-OHD, triglyceride, and total cholesterol levels were studied and 1135644 test results were taken as basis. Results: It is found that, if total cholesterol levels were above 400 mg/dL, 25-OHD levels were lower. 25-OHD levels above 100 ng/mL (considered as Vitamin D intoxication) were detected in total cholesterol levels below 400 mg/dL. There were 1538 patient samples in the groups in the 0-400 ng/dL range and no intoxication was observed in the 400-10.000 ng/dL range. The highest value (20.79±13.35 ng/mL) was found in the group with triglyceride levels between 0-99 mg/dL. It was observed that as the triglyceride level increased, 25-OHD levels decreased. Conclusions: According to this study, there is a risk of toxicity when administering vitamin D therapy in patients with high cholesterol and triglyceride levels. This study is that it is the first study of this size in the literature. High triglyceride and cholesterol levels can cause inaccurate measurement of vitamin D levels, so care should be taken when evaluating these tests.